The Utilization Of Instructional Multimedia For English Learning - Farani, Rizki (Journal of English and Education (JEE), 2011)
Technology is one of the instructional components in almost all teaching and learning processes, including English learning. However, the utilization of technology in English Learning needs specific methodological procedures to develop appropriate media for students. This paper will discuss about the utilization of instructional multimedia in English learning by describing the concept of multimedia, instructional multimedia in English learning and the application of instructional multimedia utilization in the class. The application is based on a research, conducted in STAIN (State Islamic Institute) Samarinda in March 2012. The research involves several procedures in using multimedia in Reading class. The media is CD product, developed by using software Macromedia Flash 8 and Cool Edit Pro.